Can GCSF-stimulated donor lymphocyte infusions improve outcomes for relapsed disease following allogeneic hematopoietic cell transplantation? A systematic review and meta-analysis. Issue 14 (6th December 2022) - Kirkham, Aidan M.; Bailey, Adrian J. M.; Masurekar, Ashish; Shorr, Risa; Bredeson, Christopher; Sabloff, Mitchell; Allan, David S.
Abstract: Donor lymphocyte infusions (DLI) can produce graft-versus tumor effects to treat relapse after allogeneic hematopoietic cell transplantation, however, durable responses remain uncommon. A systematic review and meta-analysis are needed to clarify whether DLI collected after stimulation with granulocyte colony-stimulating factor (GCSF; G-DLI) can improve clinical outcomes. Sixteen studies (4 controlled) involving 585 patients were identified in a systematic search up to 17 September 2020. A meta-analysis demonstrated no significant difference in the risk of all-cause mortality (RR: 0.94, 95% CI 0.52–1.68, p = 0.82; n = 3 studies) or relapse-related mortality (RR: 0.72, 0.44–1.18, p = 0.19; n = 3 studies) between G-DLI and conventional DLI (C-DLI) groups. G-DLI products had similar mean CD3+ cells compared to C-DLI products, but median CD34+ cells/kg were increased. No improvement in disease progression, complete response rates, or risk of developing GVHD was observed with G-DLI, however, greater non-relapse mortality was observed compared to C-DLI. Alternative approaches to enhancing graft-versus-tumor effects are needed.